HYPERTENSION AND RELATED FACTORS AMONG FEMALE STUDENTS AT VOCATIONAL HIGH SCHOOL BEKASI, INDONESIA - Muh. Nur Hasan Syah; Utami Wahyuningsih; Sandy Ardiansyah; Muhammad Asrullah (Media Gizi Indonesia, 2020)
Hypertension is one of non-communicable diseases which prevalence is high in Indonesia, not only among adult and elderly but also among adolescent. Hypertension can be caused by various factors including fat intake, fi ber intake and nutritional status. The purpose of this study was analyze the correlation of fat intake, fi ber intake, and obesity with hypertension among female students at Vocational high school, Bekasi, Indonesia. This was a cross sectional study among 255 female students who were selected by purposive sampling technique. Hypertension was measured using sphygmomanometer with 95 percentile cut-off based on sex, age, and body height (cut-off hypertension was > 104-115 mmHg systolic and > 62-68 mmHg diastolic blood pressure). Fat and fi ber intake were assessed using Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), and obesity was measured using digital weighing scales and microtoise. Data were analyzed by chi square test. The results showed that prevalence of female students with low f fat intake was 58,8%; low fi ber intake was 82,0%; obesity was 25,1%; and hypertension was 16,5%. There was a positive correlation between fat intake (p=0,011) and obesity (p<0,01) with hypertension but no correlation was found between fi ber intake (p=0,916) and hypertension. Fat intake and obesity were related to the hypertension in adolescents. Routine blood pressure checks and restrictions on fat intake are needed to reduce the risk of hypertension in adolescents.